(P)rescription narratives : feminist medical fiction and the failure of American censorship - Tavera, Stephanie Peebles (Edinburgh Edinburgh : Edinburgh University Press, 2022)
Examines how women writers of medical fiction rewrite cultural narratives of the female body against censorship under the Comstock Laws.
Crip medicine: Environmental health and the matter of hysteria -- Listen for the new man: From narrative prosthesis to narrative medicine -- Kinetic medicine: Superposition of Black female subjectivity before the law -- Affective fear: Vulnerability and risk in anti-VD campaign counternarratives -- Conclusion: Medical theater: The birth of anti-lynching plays and reproductive justice.
Includes bibliographical references (pages 197-209) and index.
Print version record.
JSTOR
Keywords: American fiction -- Women authors -- History and criticism; Medical fiction, American -- History and criticism; Censorship -- United States -- History; Disabilities in literature; Women with disabilities in literature; Women in literature; Human body in literature; Handicap dans la littérature.; Handicapées dans la littérature.; Femmes dans la littérature.; Corps humain dans la littérature.; LITERARY CRITICISM / Feminist; American fiction -- Women authors; Censorship; Disabilities in literature; Human body in literature; Medical fiction, American; Women in literature; Women with disabilities in literature; United States; Literature: history & criticism; Literary theory; Literary studies: fiction, novelists & prose writers; Feminism & feminist theory; Literature; Criticism, interpretation, etc; History